Survey of full-scale sidestream enhanced biological phosphorus removal (S2EBPR) systems and comparison with conventional EBPRs in North America Process stability, kinetics, and microbial populations - Onnis-Hayden, Annalisa (Water environment research : a research publication of the Water Environment Federation, 2020)
© 2019 Water Environment Federation.